Efecto de la inoculación del Ustilago scitaminae Sydow en los niveles de resistencia en 10 variedades de caña de azúcar en Tarapoto - Cavero Rojas, José Enrique (2004)
The present work of investigation was made in order to evaluate the effect of the inoculation moments of the mushroom Usti/ago scitaminea, in inoculated to the moment of the sowing and to 60 days after sowing; So it determinate the resistance of the "Sugarcane smut". It was made in a thickness soil - sandy, its ecological conditions Tropical dry Forest; it located in the Morales District, County and San Martín Region. It was development between March to September, 2003. It was leaded under the design of random Blocks with 10 treatments without arrangement and with Factorial arrangement evaluating the following agronomic parameters: Budding of buds percentage, Buds emergency, Time of emergency in days, Height plant and the incidence of the illness. Of the results concluded that the varieties of sugarcane that they showed resistance they are: Blue big house PCG12-745, Purple, Hawai 57-5174 and the variety Poj. And the varieties that they showed susceptibility are: Regency, Yellow, Chicarna 37-1933, Picurina, Habanesa and the variety Chicama 32-8560. The two forms of inoculation gave positive results in the 10 varieties studied: Regency, Habanesa, Picurina, Purple, Yellow, Poj, Chicama 32, Chicama37, Blue big house and Hawai 57.